The Role of New Tyrosine Kinase Inhibitors in Chronic Myeloid Leukemia - Pophali, Priyanka A. (Cancer J, 2016)
Imatinib mesylate was the first tyrosine kinase inhibitor (TKI) approved for the management of chronic myeloid leukemia (CML). Imatinib produces acceptable responses in ~ 60% of patients; with ~20% discontinuing therapy due to intolerance and ~20% developing drug resistance. The advent of newer TKIs’ such as, nilotinib, dasatinib, bosutinib and ponatinib have provided multiple options for patients. These agents are more potent, have unique side effect profiles and are more likely to achieve relevant milestones such as, early molecular responses (3-6 months) and optimal molecular responses (12 months). The acquisition of BCR-ABL kinase domain mutations is also reportedly lower with these drugs. Thus far, none of the randomized phase III clinical trials have shown a clinically significant survival difference between frontline imatinib versus newer TKIs’. Cost and safety issues with the newer TKIs’ such as, vascular disease with nilotinib and ponatinib and pulmonary hypertension with dasatinib have dampened the enthusiasm of using these drugs as frontline options. While the utility of new TKIs’ in the setting of imatinib failure or intolerance is clear, their use as frontline agents should factor in the age of the patient, additional comorbidities, risk stratification (Sokal score) and cost. Combination therapies and newer agents with potential to eradicate quiescent CML stem cells offer future hope.